2013
DOI: 10.1007/s12032-012-0325-6
|View full text |Cite
|
Sign up to set email alerts
|

ID1 affects the efficacy of radiotherapy in glioblastoma through inhibition of DNA repair pathways

Abstract: Glioblastoma multiforme (GBM) is characterized by poor therapeutic response and poor overall survival. It is crucial that more effective therapies be developed for the treatment of GBM. Inhibitor of DNA binding protein-1 (ID1) has been shown to maintain the self-renewal capacity of neural stem cells and might be involved in the therapeutic resistance of GBM. In the present study, we explored survival data from the The Cancer Genome Atalas database that were based on ID1 expression for patients diagnosed with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In addition, ID1 has been demonstrated to contribute to radioresistance in glioblastoma through inhibition of DNA repair pathways (34). The effect of ID1 knockdown on resistance to DDP in the GC cell lines MKN-28 and MGC-803 was examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ID1 has been demonstrated to contribute to radioresistance in glioblastoma through inhibition of DNA repair pathways (34). The effect of ID1 knockdown on resistance to DDP in the GC cell lines MKN-28 and MGC-803 was examined.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have highlighted the complex role served by members of the ID subfamily in mammalian cell fate determination (21,27,28,34). IDs are involved in numerous biological processes, including the inhibition of differentiation, and the maintenance of self-renewal and multipotency in stem cells (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…ID1 belongs to the basic helix-loop helix family of genes, which have been detected in multiple malignant tumors. In addition, the expression levels of these genes have been associated with invasive features of cancer (52,53). Increasing evidence has indicated that ID1 is upregulated in HCC samples and induces cellular proliferation.…”
Section: Ar and Inhibitor Of Differentiation 1 (Id1)mentioning
confidence: 99%
“…And the inhibition of Id1 enhances the effect of temozolomide, delays tumor recurrence, and prolongs survival [32]. But an opposite conclusion was also acquired by Guo, Q et al who found that GBM patients with high Id1 expression had better survival than patients with low Id1 expression since Id1 expression could increase the radiotherapy efficacy [116]. Same conclusion was also obtained in a study of prostate cancer.…”
Section: Id1 In Therapeutic Resistancementioning
confidence: 85%